2009
DOI: 10.1016/j.biopsych.2009.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Is Serum Brain-Derived Neurotrophic Factor a Biomarker for Cognitive Enhancement in Schizophrenia?

Abstract: Background Brain-derived neurotrophic factor (BDNF) plays a critical role in neurodevelopment and plasticity; decreased BDNF functioning may contribute to the pathogenesis of schizophrenia. However, BDNF levels are not static; in animal experiments, brain BDNF increases during spatial learning, and in clinical depression, successful antidepressant treatment raises serum BDNF. We asked: would neuroplasticity-based cognitive training in schizophrenia result in increased serum BDNF? Methods Fifty-six schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
174
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(182 citation statements)
references
References 40 publications
7
174
0
1
Order By: Relevance
“…In our study, schizophrenic patients with reduced truncated-BDNF had worse efficency in all neurocognitive tests in relationship to the other patients with normal levels of truncated-BDNF, although the correlation between Trail Making Test Part A score and truncated-BDNF abundance do not reach the statistically significance. Our results further enlarge a recent research telling that evaluation of total serum BDNF may be useful to predict for a good outcome in neurocognitive enhancement sessions in schizophrenic patients (Vinogradov et al, 2009). Importantly, we also underline that four healthy subjects with low truncated-BDNF had poor scores in Trail Making Test B and Symbol Digit Coding attention test.…”
Section: The Role Of Probdnf In Patients With Schizophreniasupporting
confidence: 79%
“…In our study, schizophrenic patients with reduced truncated-BDNF had worse efficency in all neurocognitive tests in relationship to the other patients with normal levels of truncated-BDNF, although the correlation between Trail Making Test Part A score and truncated-BDNF abundance do not reach the statistically significance. Our results further enlarge a recent research telling that evaluation of total serum BDNF may be useful to predict for a good outcome in neurocognitive enhancement sessions in schizophrenic patients (Vinogradov et al, 2009). Importantly, we also underline that four healthy subjects with low truncated-BDNF had poor scores in Trail Making Test B and Symbol Digit Coding attention test.…”
Section: The Role Of Probdnf In Patients With Schizophreniasupporting
confidence: 79%
“…Recent studies suggested that concentrations of BDNF protein in the blood (serum or plasma) may represent peripheral manifestation of depression (48) and schizophrenia (49) and could be used as a biomarker for therapeutic efficacy (50). Similarly, BDNF DNA methylation changes have been found in the peripheral blood of patients suffering from depression (13), bipolar disorder (12), schizophrenia (14), and eating disorders (51), and a change in BDNF DNA methylation status correlated with a positive response to psychotherapy in borderline personality disorder (52).…”
Section: Discussionmentioning
confidence: 99%
“…For example, cognitive training has been shown to be associated with increases in serum BDNF, which is known to have a role in neuronal development (Vinogradov et al, 2009). This suggests that behavioral changes following training may be the result of functional plasticity, as distinct from increased automated processing following repetitive practice.…”
Section: Introductionmentioning
confidence: 99%